1990
DOI: 10.1111/j.1476-5381.1990.tb12987.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of 5‐hydroxytryptamine agonists and antagonists on identified sympathetic preganglionic neurones in the rat, in vivo

Abstract: 1 5-Hydroxytryptamine (5-HT) was applied by microiontophoresis in the vicinity of identified sympathetic preganglionic neurones in the upper thoracic spinal cord of the rat, in vivo. 2 Sympathetic preganglionic neurones responded in one of three ways to 5-HT: by (a) excitation (76%), (b) inhibition (4%) or (c) in a biphasic manner (5%). 3 The excitatory responses evoked by 5-HT were mimicked by 5-carboxamidotryptamine (5-CT) and a-methyl-5-hydroxytryptamine (a-Me-5-HT). The inhibitory and biphasic responses ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…Experiments were undertaken on twenty-eight male Lewis & Coote, 1990). All three muscle pools were filled with paraffin (BDH, Poole, UK) maintained at 37 'C.…”
Section: Methods Animals and Surgerymentioning
confidence: 99%
“…Experiments were undertaken on twenty-eight male Lewis & Coote, 1990). All three muscle pools were filled with paraffin (BDH, Poole, UK) maintained at 37 'C.…”
Section: Methods Animals and Surgerymentioning
confidence: 99%
“…It is also apparent, on the basis of the preceding description, that through different receptor populations, 5-HT could have divergent effects on different populations of neurons in the serially connected organization of the central pathways determining the sympathetic and vagal outputs controlling blood pressure. Thus, if 5-HT has simultaneous access to inhibitory 5-HT receptors (such as 5-HT 1A receptors) on sympathetic premotor neurons and stimulatory 5-HT receptors (such as 5-HT 2A receptors) on sympathetic preganglionic neurons, it is not surprising that administration of serotonin can either inhibit or stimulate preganglionic sympathetic nerves (Lewis and Coote, 1990). Moreover, Pickering et al (1994) showed that perfusion of a spinal cord slice preparation with 5-HT induced rhythmic activity in sympathetic preganglionic neurons.…”
Section: -Ht and Blood Pressurementioning
confidence: 99%
“…Furthermore, the 5-HT and noradrenaline re-uptake inhibitor, duloxetine, has been shown to produce increases in external urethral sphincter EMG activity that were reversed by the nonselective 5-HT receptor antagonist, methiothepin and by the 5-HT2 receptor subtype selective antagonist, 4-isopropyl-7-methyl -9-(2-hydroxy-1-methylpropoxycarbonyl)- 4,6,6A,7,8,9,10, 10A-octahydroindolo-[4,3-fg] quinoline maleate, (LY53857; Thor & Katofiasc, 1995). An involvement of 5-hydroxytryptaminergic systems in regulation of sympathetic neural activity is also well-established (deGroat & Ryall, 1967;McCall, 1984;Lewis & Coote, 1990;Helke et al, 1991), but the specific receptor subtypes mediating various effects are not well-defined.…”
Section: Introductionmentioning
confidence: 99%